Epstein–Barr Virus and Human Papillomaviruses Interactions and Their Roles in the Initiation of Epithelial–Mesenchymal Transition and Cancer Progression - Cyprian, Farhan S.; Al-Farsi, Halema F.; Vranic, Semir; Akhtar, Saghir; Al Moustafa, Ala-Eddin (Frontiers in Oncology, 2018)
Oncoviruses are implicated in around 20% of all human cancers including both solid and non-solid malignancies. Epstein-Barr virus (EBV) and human papillomaviruses (HPVs) are the most common oncoviruses worldwide. Currently, it is well established that onco-proteins of EBV (LMP1, LMP2A and EBNA1) and high-risk HPVs (E5 and E6/E7) play an important role in the initiation and/or progression of several human carcinomas including cervical, oral and breast. More significantly, it has been recently pointed out that viral onco-proteins of EBV and high-risk HPVs can be co-present and consequently cooperate to initiate and/or amplify epithelial-mesenchymal transition (EMT), which is the hallmark of cancer progression and metastasis. This could occur by -catenin, JAK/STAT/SRC, PI3k/Akt/mTOR and/or RAS/MEK/ERK signaling pathways, which onco-proteins of EBV and HPVs share. This review presents the most recent advances related to EBV and high-risk HPVs onco-proteins interactions and their roles in the progression of human carcinomas especially oral and breast via the initiation of EMT.